Wartość komentarza w przekładzie (na przykładzie literatury słoweńskiej) - Gawlak, Monika (Przekłady Literatur Słowiańskich, 2017)
The Value of Comment in Translation: the Example of Slovenian Literature The article deals with the role of comment (as a kind of paratext), which gains a particular status in translation, becoming an additional medium between the author/translator/editor and the primary text and the secondary recipient as well as their cultural universe. This seems important because the translated text is to function in a new environment, a new cultural space; it is supposed to find its way to a new audience, and thus this type of expressions “support” translation in its most important role of a link in cross-cultural communication. The role, nature, and importance of paratext-comments (introductions, prefaces, postscripts) have been examined in the context of translations of Slovenian literature in Poland basing on selected examples. Both the comments of experts-researchers, as well as interpreters themselves, have been taken into consideration. The author notes that, from the ethical point of view, a commentary becomes contributive to the slow process of the recipient realizing the presence of an interpreter and inter-subjective nature of translation, extracts the unfamiliar categories of perception and understanding of the world, brings them closer, making the gesture of seeking “imagined communities”. Keywords: paratext, comment, translation, Slovenian literature, cross-cultural communication